Psychosocial stress and immunosuppression in cancer: what can we learn from new research?. (May 2021) - Singh, Anurag K.; Chatterjee, Udit; MacDonald, Cameron R.; Repasky, Elizabeth A.; Halbreich, Uriel
SUMMARY: It is generally believed that the physiological consequences of stress could contribute to poor outcomes for patients being treated for cancer. However, despite preclinical and clinical evidence suggesting that stress promotes increased cancer-related mortality, a comprehensive understanding of the mechanisms involved in mediating these effects does not yet exist. We reviewed 47 clinical studies published between 2007 and 2020 to determine whether psychosocial stress affects clinical outcomes in cancer: 6.4% of studies showed a protective effect; 44.6% showed a harmful effect; 48.9% showed no association. These data suggest that psychosocial stress could affect cancer incidence and/or mortality, but the association is unclear. To shed light on this potentially important relationship, objective biomarkers of stress are needed to more accurately evaluate levels of stress and its downstream effects. As a potential candidate, the neuroendocrine signalling pathways initiated by stress are known to affect anti-tumour immune cells, and here we summarise how this may promote an immunosuppressive, pro-tumour microenvironment. Further research must be done to understand the relationships between stress and immunity to more accurately measure how stress affects cancer progression and outcome.